Optimizing Urban Mobility: Assessing the Impact of Selangor's Intelligent Transport System (SITs) - Binti Abd Nasir, Siti Muyassarah; Binti Mohamood, Siti Khairul Bariah (Department of Informatics, Universitas Syiah Kuala, 2024)
This paper addresses Malaysia's public transport system, primarily managed by small operators in its developing state. Efficient transportation management relies on collaborative information sharing. Systems must provide an easy and effective way to manage staff and registered users, including students and community members. Working passengers require efficient route information to minimize delays. Therefore, systems should cater to all users' needs. Registered users, such as students, also require real-time bus updates to avoid long waits and inform the organization of delays via SMS. Implementing and managing these services collectively presents challenges. Mobile technology, including smartphones and laptops, offers a solution through location-based applications for managing transportation with map navigation. The recent mobile technology revolution has intensified competition among developers, resulting in similar yet distinct applications. Modern transit services now offer virtual access to schedules and advanced features like integration with Google Maps and real-time tracking. De-spite benefits, implementing a Smart Transportation Application (STA) with GPS and digital route maps can be daunting and costly for smaller operators.